(untitled) (Revista Brasileira Multidisciplinar, 2015)
The Escherichia coli research and Salmonella spp. in foods is an important hygienic-sanitary bioindicator, indicating fecal contamination. The sausage has a very easy preparation and consumption, however, if handled improperly, can become an excellent source of contamination and proliferation of micro-organisms. To analyze the presence of these bacteria, 32 samples of sausage were collected in large and small supermarket. The quantitative microbiological analysis for Escherichia coli was made in EMB agar, and for Salmonella, in SS agar. Suspect colonies were identified by biochemical tests. Of the total samples, 50% showed growth of Escherichia coli and Salmonella spp. presented no growth. These data demonstrate the necessity for a greater hygienic sanitary inspection in commercial establishments and a greater attention of the population to the food which is being ingested.